Passiflora incarnata extract-induced VEGF and TGF-β1 mRNA expression in the cardiovascular system using the rat model of type 2 diabetes - Wesołowska, Anna; Ożarowski, Marcin; Mikołajczak, Przemysław Ł.; Stelmaszyk, Agnieszka; Maliszewska-Dworacka, Anna; Iskakova, Saule; Frycz, Bartosz A.; Jagodziński, Paweł P.; Dworacka, Marzena (Journal of Medical Science, 2025)
Aim. To investigate the possible effects of Passiflora extract on VEGF and TGF-β1 mRNA expression – growth factors closely related to the development of diabetes in the cardiovascular system.Material and methods. The animal model of type 2 diabetes, rich-fat/STZ Wistar rats, was used. Animals were randomised into four groups: Passiflora-treated type 2 diabetes mellitus model group; metformin-treated type 2 diabetes mellitus model group; placebo-treated type 2 diabetes mellitus model group; and placebo-treated non-diabetic control group. Passiflora incarnata leaf extract was administered orally once daily for eight consecutive weeks. mRNA VEGF, VEGF-R1, VEGF-R2 and TGF-β1 expression were measured in the myocardium and the aorta.Results. Passiflora incarnata extract increases VEGF and VEGFR2 mRNA expression in the myocardium of rats with type 2 diabetes and decreases expression in the aortal wall. The expression of TGF-β1 mRNA in both the myocardium and the aorta is reduced in Passiflora incarnata-treated rats with diabetes. Most observed effects are independent of the animals' current metabolic status.Conclusions. The current data provide novel findings on the beneficial effects of Passiflora extract on the myocardium in the context of type 2 diabetes, potentially through mechanisms involving VEGF and TGF-β1. However, the significance of the impact of Passiflora extract on the aorta wall via VEGF and TGF-β1 is uncertain.
Keywords: Passiflora incarnata; vascular endothelial growth factor; vascular endothelial growth factor receptors; transforming growth factor β1; type 2 diabetes mellitus